Fiscal Regimes for Extractive Industries-Design and Implementation. (Policy Papers; Policy Paper, 2012)
Better designed and implemented fiscal regimes for oil, gas, and mining can make a substantial contribution to the revenue needs of many developing countries while ensuring an attractive return for investors, according to a new policy paper from the International Monetary Fund. Revenues from extractive industries (EIs) have major macroeconomic implications. The EIs account for over half of government revenues in many petroleum-rich countries, and for over 20 percent in mining countries. About one-third of IMF member countries find (or could find) resource revenues 'macro-critical' - especially with large numbers of recent new discoveries and planned oil, gas, and mining developments. IMF policy advice and technical assistance in the field has massively expanded in recent years - driven by demand from member countries and supported by increased donor finance. The paper sets out the analytical framework underpinning, and key elements of, the country-specific advice given. Also available in Arabic: Also available in French: Regimes fiscaux des industries extractives: conception et application Also available in Spanish: Regimenes fiscales de las industrias extractivas: Diseno y aplicacion.